Ecological hermeneutics as a current trend in Old Testament research in the Book of Psalms - H. Ferreira; L. Sutton (Acta Theologica)
This article addresses an urgent ecological crisis of this century. It explores the transformative potential of ecological hermeneutics as a current trend in Old Testament research in the context of the Book of salms. As we face the unprecedented ecological threat of global devastation, this article identifies a new kind of speech emerging from current ecological trends in biblical research. The article examines the historical implications of biblical texts in the discussion about ecological degradation by providing an overview of the development of ecological hermeneutics. It then presents methodologies such as dark green religion and the ecobosadi approach and advocates for ways in which they reshape culture and have the potential to play a crucial role in reshaping it.